Cognitive Behavior Therapy-Based Music (CBT-Music) view an Academic Anxiety as a Cognitive Distortion caused by Maladaptive Core Belief - Situmorang, Dominikus David Biondi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Cognitive Behavior Therapy-Based Music (CBT-Music) typically has a special view of academic anxiety experienced by students. This approach sees that the problem is a cognitive distortion caused by maladaptive core beliefs. Therefore, students who experience it need to get help so that their core beliefs can be more adaptive again. Based on the latest research results, integration of CBT counseling with modern techniques of music therapy has proved effective in reducing academic anxiety and improving self-efficacy of students. Thus, through this conceptual study, it is hoped that counselors in Indonesia will be able to understand, practice, and conduct further research on CBT counseling interventions integrated with music therapy.Key words: counseling, cognitive behavior therapy, based music, cbt-music, music therapy, academic anxiety, cognitive distortion, maladaptive core belief, the undergraduate thesis